Visual methods in social research - Banks, Marcus; Zeitlyn, David (Los Angeles SAGE Publications Ltd, 2015)
"Combining the theoretical, practical and technical the authors discuss changing technologies, the role of the internet and the impact of social media. Presenting an interdisciplinary guide to visual methods they explore both the creation and interpretation of visual images and their use within different methodological approaches."--Back cover.
1.1. The trouble with pictures -- 1.2.An introductory example -- 1.3.Unnatural vision -- 1.4.Reading narratives -- 1.4.1.Formal readings -- 1.5.Planning a research project with visual methods -- 2.1.On television -- 2.2.Visual forms produced I: representations of society -- 2.2.1.Interpreting Forest of Bliss -- 2.2.2.Still and moving images -- 2.3.Visual forms produced II: representations of knowledge -- 2.3.1.Visualization -- 2.3.2.Networks -- 2.3.3.Diagrams of Nuer lineages -- 2.4.Visual forms encountered -- 2.4.1.Encountering 'indigenous' media -- 2.4.2.The image as evidence -- 2.5.'Us' and 'them'? -- 3.1.Object and representation -- 3.2.The materiality of visual forms -- 3.2.1.Displaying family photographs -- 3.3.Exchanged goods -- 3.3.1.Market exchange -- 3.4.Size matters -- 3.5.Transformations: digitization and computer-based media -- 3.5.1.Digital manipulation -- 3.5.2.Digital pornography: constraining the virtual -- 3.5.3.Digital pornography: exchange and circulation -- 4.1.Silk thread to plastic bags -- 4.2.Researching image use and production in social contexts -- 4.3.Watching television -- 4.3.1.Soap opera in India and Egypt -- 4.3.2.Television as a social presence -- 4.4.Doing things with photographs and films -- 4.4.1.Photo-elicitation with archival images -- 4.4.2.Photo-elicitation with contemporary images -- 4.4.3.Learning from photo-elicitation -- 4.4.4.Film-elicitation -- 4.5.Working with archival material -- 4.5.1.Photographic archives and picture libraries -- 4.5.2.Film archives -- 5.1.Observing -- 5.2.Creating images for research -- 5.3.Documentation -- 5.3.1.A ladder climbed then discarded -- 5.3.2.Documentary exploration -- 5.3.3.Documentary control -- 5.4.Collaborative projects -- 5.5.Indigenous media collaborations -- 5.5.1.Collaborative after-effects -- 5.6.Ethics and visual research -- 5.6.1.Ethical review -- 5.6.2.Permissions -- 5.7.Returning images -- 6.1.Audiences -- 6.2.Presenting photographs -- 6.2.1.The photographic essay -- 6.3.Presenting ethnographic and other films -- 6.3.1.Study guides and other contextualization -- 6.4.Databases and digital images -- 6.4.1.Can computers see? -- 6.5.Multimedia projects -- 6.5.1.Interacting with the Yanomamo -- 6.6.Copyright -- 7.1.The state of visual research -- 7.2.The place of visual research -- 7.3.The nature of visual research.
Previous edition: 2001.
Mae Claire G. Jabines (Recommending faculty) - Bookfair2017
Includes bibliographical references (pages 168-181), filmography (pages 182-183), and index.
Keywords: Visual sociology; Visual anthropology; Photography in the social sciences; Social sciences -- Research -- Methodology; Social sciences -- Research -- Electronic information resources